The expansion of natural gas infrastructure puts energy transitions at risk - Claudia Kemfert; Fabian Präger; Isabell Braunger; Franziska M. Hoffart; Hanna Brauers (Nature Energy, 2022)
Whether additional natural gas infrastructure is needed or would be detrimental to achieving climate protection goals is currently highly controversial. Here we combine five perspectives to argue why expansion of the natural gas infrastructure hinders a renewable energy future and is no bridge technology. We highlight that natural gas is a fossil fuel with a significantly underestimated climate impact that hinders decarbonization through carbon lock-in and stranded assets. We propose five ways to avoid common shortcomings for countries that are developing strategies for greenhouse gas reduction: manage methane emissions of the entire natural gas value chain, revise assumptions of scenario analyses with new research insights on greenhouse gas emissions related to natural gas, replace the `bridge' narrative with unambiguous decarbonization criteria, avoid additional natural gas lock-ins and methane leakage, and take climate-related risks in energy infrastructure planning seriously.
Keywords: 320; economics; energy infrastructure; political economy of energy